2021
DOI: 10.3390/jcm10102097
|View full text |Cite
|
Sign up to set email alerts
|

Does Statin Therapy Reduce the Risks of Mortality and Major Adverse Cardiac and Cerebrovascular Events in Young Adults with End-Stage Renal Disease? Population-Based Cohort Study

Abstract: Among hemodialysis patients aged more than 40 years old, previous large-scale studies showed statin treatment had no effect on reducing cardiovascular adverse events. However, young-adult-onset end-stage renal disease (ESRD) patients have different physicosocial factors compared to older ESRD patients. The benefit of statins in such a specific group has not been well evaluated. Through the use of Taiwan’s National Health Insurance Research Database (NHIRD), young adult patients aged 20–40 with incident ESRD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…7 Similar findings were observed in patients with ESKD in whom the cardiovascular protective effect of statins was lost. [50][51][52][53] Previously published randomized clinical trials and real-world observational studies [50][51][52][53] revealed that use of statins for patients with ESKD or stage 5 CKD who were not receiving dialysis did not provide cardiovascular benefit. Gupta et al 54 reported that a statin prescription was associated with a lower risk of sepsis events.…”
Section: Jama Network Open | Diabetes and Endocrinologymentioning
confidence: 99%
“…7 Similar findings were observed in patients with ESKD in whom the cardiovascular protective effect of statins was lost. [50][51][52][53] Previously published randomized clinical trials and real-world observational studies [50][51][52][53] revealed that use of statins for patients with ESKD or stage 5 CKD who were not receiving dialysis did not provide cardiovascular benefit. Gupta et al 54 reported that a statin prescription was associated with a lower risk of sepsis events.…”
Section: Jama Network Open | Diabetes and Endocrinologymentioning
confidence: 99%
“…A total of 665 citations were identified, and 210 potentially eligible articles were retrieved in full text. Overall, 54 studies were included in the review ( Figure 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Risk of bias assessment using NOS showed that the studies have low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Although the data derived from the NHI program were initially for administrative purposes, it contained detailed information regarding enrollees’ demographics, diagnoses, prescriptions, procedures, outpatient visits, and hospitalizations. Numerous observational studies have been published using NHIRD, including those associated with statins use [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%